Influence of muscle fatigue on contractile twitch characteristics in persons with parkinson's disease and older adults: A pilot study. (2021) - Hammond, Kelley G.; Magrini, Mitchel A.; Siedlik, Jacob A.; Bickel, C. Scott; Bamman, Marcas M.
Highlights: PD skeletal muscle contractile characteristics differ from normal aging. Evoked rate of torque development during fatiguing exercise is affected by PD. Peripheral adaptations to PD result in skeletal muscle fatigue-resistance. Abstract: Introduction: It is widely accepted that pathophysiological changes to the central nervous system of persons with Parkinson's disease (PD) result in negative effects on motor function. However, less information is known regarding the pathology of PD on skeletal muscle. The purpose of this study was to determine the effect of a fatiguing isometric knee extension protocol on muscle mechanics using evoked twitch contractions in persons with PD and in non-impaired older adults (OLD). Methods: Evoked twitch contractions were examined during a fatiguing protocol in PD (66 ± 9 yr, n = 8) and OLD (65 ± 10 yr, n = 5). Participants performed 5-sec maximal isometric voluntary contractions of the quadriceps femoris with 5-sec rest for 3-min. Every 30-sec during rest intervals, a maximal transcutaneous electrical stimulus was administered to the quadriceps femoris to quantify evoked peak twitch torque (pTT), peak relaxation rate (pRR), and peak rate of torque development (pRTD). Results: A large effect of voluntary fatigue (%decline) was observed ( g  = 1.58). There were no significant differences in pTT (p = 0.09; 95% CI:-3.6, 0.28) or pRR (p = 0.11; 95% CI:-31, 3.6). However, the slope decline of pRTD in OLD (-35.4 ± 24.7) was greater than PD (-11.5 ± 11.4; p = 0.03), indicating that skeletal muscle in persons with PD is less fatigable compared to non-impaired older adults. Conclusion: The rate, not the maximum capacity, of torque generation of the muscle during a fatiguing knee extension protocol was affected by PD. Future studies are warranted to identify the mechanism(s) responsible for the observed differences in skeletal muscle contractile characteristics and potential myofiber distribution variation in PD.